Meningkatkan Keterampilan Literasi pada Siswa SD melalui Pendekatan Pembelajaran yang Inklusif - Samudra, Andika; Azri, Raihana Putri Eka; Viktres, Hilma Hidayati; Wardani, Nuraisyah (Lembaga Yasin AlSys, 2023)
This research aims to explore the effectiveness of inclusive learning approaches in improving students' literacy skills in Elementary Schools (SD). Literacy is a key component in education that plays a crucial role in shaping the foundation of lifelong learning for students. However, various factors such as different ability levels, diverse learning styles, and variations in social and cultural backgrounds often hinder students from achieving optimal literacy levels. In this study, an inclusive learning approach was adopted to create a learning environment that accommodates the needs and individual differences of each student. The research method used was Classroom Action Research (PTK) involving several classes in an elementary school. Data were collected through pre-and post-literacy tests, classroom observations, and interviews with teachers and students. The results of the study show that the inclusive learning approach has a significant positive impact on improving students' literacy skills. When students are empowered to learn in an inclusive environment, they tend to show better improvements in reading, writing, and text comprehension. Additionally, students also demonstrate increased active participation and motivation in learning, as they feel valued and supported throughout the learning process. The findings of this research underscore the importance of creating inclusive and supportive learning environments for students in SD. Teachers and educational institutions should strive to identify individual student needs, provide appropriate support, and employ diverse teaching methods to facilitate improved literacy skills. Thus, inclusive learning approaches can be an effective means to enhance the quality of education and create a brighter future for SD students in facing the challenges of a knowledge-based society.